Saúde mental e racismo: saberes e saber-fazer desnorteado na/para a Reforma Psiquiátrica brasileira antimanicolonial - David, Emiliano de Camargo (2022)
This thesis is conducted under the assumption that the manicomialization in Brazil is rooted in coloniality. Based on this premise, the aim of this research was to map antiracist knowledge and practices in mental health committed to the critical analysis of ethnic-racial relations, regarding the production of health of the black population, which we understand as the decolonization of the Psychosocial Care Network. In order to embody decolonization, three main key ideas were addressed: bewilderment, gathering in quilombo and the antimanicolonial. Each one is organized in a chapter of this research; the first chapter seeks clues for a bewildered mental health, through the dialogue with Achille Mbembe and Frantz Fanon and through the theories of Lélia Gonzales, Beatriz Nascimento, and Paul Gilroy, aiming to propose an Atlantic (dis)orientation that takes into consideration aspects of the black diaspora and of Latin America (Ladin Amefrica) that can re-signify blackness and unreason beyond the psychopathologization and the fixation on race. The second chapter traces the path of the aquilombar, based on Abdias do Nascimento's Quilombismo; Clóvis Moura's Quilombagem; Beatriz Nascimento's (K)Quilombo and Mariléa de Almeida's Devir Quilomba. In the third, some itineraries of mental health construction of the black population in the course of the implementation of the Health of the Black Population are presented. A timeline and a map of the national/federal, São Paulo state and São Paulo municipal scenarios allow us to recognize the tensions and challenges of this implementation and the need for the radicalization of the Psychiatric Reform, through the aquilombation of the anti-asylum struggle. Finally, three antiracist mental health groups were monitored, namely: Kilombrasa, Café Preto and Aquilombamento das Margens, which have been developing their actions in the Psychosocial Care Network of the Municipality of São Paulo and Greater São Paulo. In order to understand the dynamics of the functioning of each collective, the methodological perspective of cartographic intervention research was chosen which allowed us to use different monitoring procedures – visits to mental health services in antiracist actions, virtual interviews and conversation circles, recordings and transcriptions of meetings/ reunions, field diary annotations and photographic records. Part of the collected materials are presented in the form of narrative fragments, which condense the power plays of the anti-racist mental health experiences produced in these meetings/actions. Anchored in this bewildering theoretical referential and in the experiences of aquilombation in the Psychosocial Care Network, this research proposes the radicality in mental health care from the anti-asylum struggle